Socioeconomic status and anthropometric changes—A meta‐analytic approach from seven German cohorts - Herzog, Beatrice; Lacruz, Maria E.; Haerting, Johannes; Hartwig, Saskia; Tiller, Daniel; Medenwald, Daniel; Vogt, Susanne; Thorand, Barbara; Holle, Rolf; Bachlechner, Ursula; Boeing, Heiner; Merz, Benedikt; et al. (Obesity (Silver Spring, Md.), 2016)
Objective To study the association between socioeconomic status (SES) and annual relative change in anthropometric markers in the general German adult population. Methods Longitudinal data of 56,556 participants aged 18–83 years from seven population‐based German cohort studies (CARLA, SHIP, KORA, DEGS, EPIC‐Heidelberg, EPIC‐Potsdam, PopGen) were analyzed by meta‐analysis using a random‐effects model. The indicators of SES were education and household income. Results On average, all participants gained weight and increased their waist circumference over the study's follow‐up period. Men and women in the low education group had a 0.1 percentage points greater annual increase in weight (95% CI men: 0.06‐0.20; and women: 0.06‐0.12) and waist circumference (95% CI men: 0.01‐0.45; and women: 0.05‐0.22) than participants in the high education group. Women with low income had a 0.1 percentage points higher annual increase in weight (95% CI 0.00‐0.15) and waist circumference (95% CI 0.00‐0.14) than women with high income. No association was found for men between income and obesity markers. Conclusions Participants with lower SES (education and for women also income) gained more weight and waist circumference than those with higher SES. These results underline the necessity to evaluate the risk of weight gain based on SES to develop more effective preventive measures.